Athlete health and safety at large sporting events: the development of consensus-driven guidelines. Issue 4 (12th November 2020) - Mountjoy, Margo; Moran, Jane; Ahmed, Hosny; Bermon, Stephane; Bigard, Xavier; Doerr, Dominik; Lacoste, Alain; Miller, Stuart; Weber, Alexis; Foster, Jeremy; Budgett, Richard; Engebretsen, Lars; et al.
Abstract : All sport events have inherent injury and illness risks for participants. Healthcare services for sport events should be planned and delivered to mitigate these risks which is the ethical responsibility of all sport event organisers. The objective of this paper was to develop consensus-driven guidelines describing the basic standards of services necessary to protect athlete health and safety during large sporting events. By using the Knowledge Translation Scheme Framework, a gap in International Federation healthcare programming for sport events was identified. Event healthcare content areas were determined through a narrative review of the scientific literature. Content experts were systematically identified. Following a literature search, an iterative consensus process was undertaken. The outcome document was written by the knowledge translation expert writing group, with the assistance of a focus group consisting of a cohort of International Federation Medical Chairpersons. Athletes were recruited to review and provide comment. The Healthcare Guidelines for International Federation Events document was developed including content-related to (i) pre-event planning (eg, sport medical risk assessment, public health requirements, environmental considerations), (ii) event safety (eg, venue medical services, emergency action plan, emergency transport, safety and security) and (iii) additional considerations (eg, event health research, spectator medical services). We developed a generic standardised template guide to facilitate the planning and delivery of medical services at international sport events. The organisers of medical services should adapt, evaluate and modify this guide to meet the sport-specific local context.